PEMBINAAN ANAK SECARA DINt UNTUK MENCAPAI PRESTASI OLAHRAGA - Sumaryanto Sumaryanto (Jurnal Cakrawala Pendidikan, 2001)
The effort to raising-up the children"s sport perfonnance should be carried out to developing their wishes early. It was be necessary carried out on the demand of childrens growing and developing that occurred at their little-young phases that could be influenced onto their life in the next phases. The varioustly forms in which containposilively valuable should be provide to the children. The playinlg activities will be either activity forms that could be applied on the way to developing lh~jl wishes early. With the finely and carefully playing activities organizing, the children will obtain some advantages such as physic~ physiologist and psychologist advantages. By this reason the playing activities becomes to the fully capahility educating ideas that can provide the opportunities for the children to growing and developing the all of their personal nature. Laterit was providing the best result to  increase the children's perfonnance, especially in the sport